2016
DOI: 10.1016/j.envres.2016.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Using spatio-temporal modeling for exposure assessment in an investigation of fine particulate air pollution and cardiovascular mortality

Abstract: The application of finer scale geographically resolved AP exposures made it possible to study acute effects of PM on CVD mortality in a large metropolitan area. Our study results demonstrated the continued presence of a dose response relationship of increased risk of CVD mortality within this lower range of PM exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 23 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…We argue that pregnant populations exposed to air pollution should be reclassified as at‐risk populations under the current NAAQS. In non‐gravid human populations, exposure to pollutants such as PM has been associated with increased cardiovascular mortality (Dabass et al, ; Krewski et al, ; Miller et al, ; Pope, Burnett, & Thurston, ) and morbidity, including onset of atrial fibrillation (Lin, Liu, Le, & Hwang, ) and decrease in high density lipoprotein functionality (Ramanathan et al, ). Similarly, ozone exposure has been associated with increased cardiovascular mortality among humans (Cakmak, Hebbern, Vanos, Crouse, & Burnett, ).…”
Section: Introductionmentioning
confidence: 99%
“…We argue that pregnant populations exposed to air pollution should be reclassified as at‐risk populations under the current NAAQS. In non‐gravid human populations, exposure to pollutants such as PM has been associated with increased cardiovascular mortality (Dabass et al, ; Krewski et al, ; Miller et al, ; Pope, Burnett, & Thurston, ) and morbidity, including onset of atrial fibrillation (Lin, Liu, Le, & Hwang, ) and decrease in high density lipoprotein functionality (Ramanathan et al, ). Similarly, ozone exposure has been associated with increased cardiovascular mortality among humans (Cakmak, Hebbern, Vanos, Crouse, & Burnett, ).…”
Section: Introductionmentioning
confidence: 99%
“…8,12,13 Many health assessment studies showed an association between ambient PM 2.5 levels and their impacts on cardio-respiratory mortality. [14][15][16][17][18] A long-term exposure to ambient PM 2.5 can cause deaths for ischemic heart diseases and chronic obstructive pulmonary diseases. 19,20 The ischemic heart diseases (IHD) is a cardiovascular condition characterized by inability of cardiac muscles to function effectively due to poor blood circulation caused by atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Jost et al [12,13] used an interpolation method to determine the distribution of a forest ecosystem and the water storage layer near the desert; their method can assist groundwater managers to make correct decisions. Park et al [14,15] used the spatiotemporal kriging method to more accurately estimate the spread of air pollutants and the distribution of infectious diseases, adding to omissions in the data collection process.…”
Section: Introductionmentioning
confidence: 99%